Analysis of the development process of the bahir dar Teachers colledge pedagology syllabus - Nigussie, Kassahun (The Ethiopian Journal of Education, 2024)
The purpuse of this study was to analyse the development process of the bahie Dar teachers college pedagology syllabus with the intention of determining its effectiveness.